Principles Integration of Legal Certainty and Justice in Public Transportation Rates Policy - Tiyara Parengkuan; Fauzie Yusuf Hasibuan (CV. Ridwan Publisher, 2023)
Online and conventional-based public transportation rates can be adjusted to possible fairest calculation by taking into account mileage, gasoline, and spare parts maintenance, this is as well as by primarily paying attention to and considering the driver partners who are members of it. Those circumstances will create effectivity and efficiency in order to have stable economy for Indonesia and the people. This study uses a normative juridical approach with the specification of the research is descriptive analytic. The results of the study show that the conformity policy concept of economic income in transportation businesses of both online-based public transportation and conventional public that integrates the principles of legal certainty and justice must carry out a reconstruction of the provisions of Article 183 paragraph 1 of Law no. 22 of 2009 concerning Road Traffic and Transportation.